2018
DOI: 10.1002/term.2771
|View full text |Cite
|
Sign up to set email alerts
|

Temporal effects of cytokine treatment on lubricant synthesis and matrix metalloproteinase activity of fibroblast-like synoviocytes

Abstract: Fibroblast-like synoviocytes (FLS) are major contributors to the composition and function of synovial fluid (SF). In disease, changes to important SF molecules such as hyaluronic acid (HA), lubricin, and numerous inflammatory markers contribute to a loss of SF functional properties. Previous studies characterized the ability of FLS to produce SF molecules in short-term cultures using continuous cytokine supplementation. This study assessed the HA, lubricin, and matrix metalloproteinase-2 (MMP-2) secretion prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…18 Furthermore, synoviocytes are major contributors to the composition and function of synovial fluid; thus, MMPs released from synoviocytes could affect adjacent tendons, cartilage, and muscles, contributing to a vicious circle in shoulder anatomy. 1 In a similar vein to our result, Sundman et al 50 reported that using PRP in the synovium from patients with osteoarthritis reduced the gene expression of MMP-13. In our study, using PRP on IL 1b2stimulated synoviocytes, the level of matrix enzymes (MMP-1, -3, and -13 as well as ADAMTS-4 and -5) significantly decreased, whereas no significant changes were detected in their inhibitors (TIMP-1).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…18 Furthermore, synoviocytes are major contributors to the composition and function of synovial fluid; thus, MMPs released from synoviocytes could affect adjacent tendons, cartilage, and muscles, contributing to a vicious circle in shoulder anatomy. 1 In a similar vein to our result, Sundman et al 50 reported that using PRP in the synovium from patients with osteoarthritis reduced the gene expression of MMP-13. In our study, using PRP on IL 1b2stimulated synoviocytes, the level of matrix enzymes (MMP-1, -3, and -13 as well as ADAMTS-4 and -5) significantly decreased, whereas no significant changes were detected in their inhibitors (TIMP-1).…”
Section: Discussionsupporting
confidence: 89%
“…Reverse transcription and amplification were performed according to the procedures described in Appendix 9 (available online). Genes in 3 categories were assessed: (1)…”
Section: Real-time Reverse Transcription Polymerase Chain Reactionmentioning
confidence: 99%
“…HA production by synovium derived cell cultures from either OA or RA patients have been extensively studied in connection with the production of inflammatory molecules and therapeutic interventions with a variety of small molecule drugs [ 70 , 71 , 72 ] to control inflammation in a range of arthritic conditions. Furthermore, such cells have been used to examine the effect of potential therapeutic HA formulations [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…This response is not only reinitiated after surgery, but is maintained perhaps indefinitely as increased synovial concentrations of pro-inflammatory cytokines have been reported 5 years after ACL reconstruction [2]. It has been previously suggested that long-acting agents may provide a greater treatment effect as temporal regulation of cytokine activity may more successfully alter the pro-inflammatory environment than shorterduration treatments [21]. Prior studies have shown that montelukast can counteract the inflammatory environment of rheumatoid arthritis [45].…”
Section: Sustained Deliverymentioning
confidence: 99%
“…Limiting the biochemical cascade through an innovative disease-modifying treatment to target upstream activity will potentially treat all components of the knee, thereby lessening the inflammatory response, reducing cartilage catabolism, and potentially improving pathologic bony remodeling observed after ACL reconstruction. The early proteomic PTOA response is more similar to inflammatory rheumatoid arthritis than idiopathic OA [13]; thus, long-acting agents which better regulate pro-inflammatory cytokine activity may more successfully limit tissue destruction [21]. By repurposing approved therapeutics with proven immune efficacy [22], we may arrive at a readily available and costeffective strategy for disease modification.…”
Section: Introductionmentioning
confidence: 99%